Screening and bioavailability evaluation of anti-oxidative selenium-containing peptides from soybeans based on specific structures. Issue 9 (19th April 2022) - Zhang, Xing; He, Hui; Xiang, Jiqian; Hou, Tao
Abstract : SFQSeM is a potential replacement for inorganic selenium and seleno-amino acids to promote antioxidant capacity and regulate selenium toxicity. Abstract : Our previous study has evaluated the antioxidant capacity and identified the sequences of soybean selenium-containing peptides. Herein, pharmacophore screening, gastrointestinal simulation and in vivo pharmacokinetics were performed to predict the potentials of selenium-containing peptides in terms of antioxidant activity, safety and bioavailability. A pharmacophore model with 6 structure features was constructed for virtual screening to determine the potential activities of 85 selenium sequences from soybean peptides. Strong reversing effects ( p < 0.05) of the targeted sequences were observed in tumor necrosis factor-α (TNF-α)-induced inflammatory cytokines and adhesion factors burst in EA·hy926/Caco-2 co-culture cell models. Ser-Phe-Gln-SeMet (SFQSeM), a promising peptide selected from both virtual screening and cell models, was proved to be stable in the gastrointestinal tract and could be transported across the Caco-2 monolayer via the paracellular pathway. Additionally, SFQSeM showed a long residence time (89.42 ± 1.34 min) and half-life (81.60 ± 11.88 min) after consumption, and it induced lower liver alanine/aspartate transaminase (ALT/AST) and serum nitric oxide (NO) levels compared to Na2 SeO3 and SeMet ( p < 0.05). The potency of SFQSeM against oxidative stress as well as its oral bioavailability and low risk highlight its potential utility as an effective Se nutritional supplement.